PENGARUH KONSUMSI BUAH NAGA TERHADAP TEKANAN DARAH PADA IBU HAMIL - Noorhayati Maslani; Rubiati Hipni; Isnaniah Isnaniah (Jurnal Inovasi Penelitian, 2021)
Pregnant women are declared anemic if hemoglobin (Hb) <11 mg / L While hypertension occurs usually in the last month of pregnancy or more after 20 weeks of gestational age in women who were previously normotensive, blood pressure reaches a value of 140/90 mmHg, or an increase in systolic pressure of 30 mmHg and a diastolic pressure of 15 mmHg above the normal value. Based on the results of the Basic Health Research (Riskesdas) in 2013, the prevalence of anemia in pregnant women in Indonesia was 37.1%, while the incidence of anemia in Banjarmasin from January to July 2018 was 1,160 people where there was the highest among pregnant women with anemia in the Alalak Central Health Center area, 176 people (22.80%) and pregnant women with hypertension, 20 people out of 572 pregnant women (3.49%). (Banjarmasin City Health Office Data 2018). Red dragon fruit contains iron and has properties to reduce blood pressure, reduce blood sugar levels, and antioxidants. The purpose of this study was to analyze the effect of dragon fruit consumption on hemoglobin levels and blood pressure on pregnant women. The research design used was experimental (experimental), with the type of posttest only control group design, in which the researcher measured the effect of treatment on the experimental group by comparing the control group. The total sample of 30 respondents in pregnant women consisting of 15 treatment groups were given dragon fruit as much as 500 mg / day for 7 days and 15 control groups. The analysis used was the one way ANOVA test.Conclusion: The administration of red dragon fruit has an effect on increasing Hb levels but has no effect on reducing blood pressure in pregnant women.